A preliminary study on the geological conditions and indexes for the accumulation of shale gas in the marine-continental transitional facies sediments in the South North China Basin - Peng, Yicong; Pan, Jishun; An, Xifeng (Frontiers in Earth Science, 2022)
At present, the Carboniferous-Permian shale gas in the South North China Basin is still in the exploration stage, and the understanding of the microscopic pore structures, mineral composition and hydrocarbon enrichment law of the marine-continental transitional shale gas reservoirs in this area is extremely limited. In this paper, taking the Carboniferous-Permian shale gas reservoir in the South North China Basin as an example, the geological conditions of shale gas accumulation in the basin have been systematically studied using a large amount of sedimentary, logging, seismic, core, geochemical, physical properties, and scanning electron microscope data. The study shows that the transitional dark shale is stable and widely distributed in the South North China Basin. Among them, the thickness of the high-quality shale of the Taiyuan Formation is about 67 m, while that of the Shanxi Formation is about 56 m. Carboniferous and Permian are the main strata for the distribution of shale gas resources. Among them, the dark shale developed in the Taiyuan and the Shanxi Formations has the largest thickness and the highest organic matter abundance. In addition, the organic matter types of the Upper Paleozoic coal-measure source rocks in the South North China are mainly II2-III types, and a small part of them belong to II1 types. The brittle minerals in the target shale are mainly quartz, and the content of illite is the highest among the clay minerals. Porosity is negatively correlated with clay mineral content, and positively correlated with quartz content and TOC content. In addition, the permeability is negatively correlated with the organic matter content. Finally, the criteria for key indicators of transitional shale gas reservoirs in the South North China Basin were developed.